STRUCTURAL ANALYSIS OF SPRAY-DRIED COCONUT SHELL LIQUID SMOKE POWDER [Analisis Struktural Bubuk Asap Cair Batok Kelapa Hasil Pengeringan Semprot] - Satrijo Saloko; Purnama Darmadji; Bambang Setiaji; Yudi Pranoto (Jurnal Teknologi dan Industri Pangan, 2012)
The research was aimed at determining spray drying conditions during the production of smoke particulate powder and its consequences on the physical properties of the product. The experiment was carried out using a complete randomized factorial design. Samples were three solution of chitosan (CS)-maltodextrin (MD) based nanoparticles i.e. CS (0.5% w/v) and MD (9.5% w/v) in acetic acid (1.0% v/v) without liquid smoke (F1), only MD (10% w/v) in liquid smoke (F2) and a mixture of CS (1.5% w/v) and MD (8.5% w/v) in liquid smoke (F5). Each sample solution was prepared at 10% solid contents with addition of 1.0% sodium tripolyphosphate. The experimental factors were inlet air temperatures (T) of 130°C (T1) and 150°C (T2) and feed flow rate (L) of 2.4 mL/minute (L1) and 5.1 mL/minute (L2). The parameters evaluated included bulk density, yield, moisture content, water activity, morphology and particle size. Results showed that the average particle sizes decreased when the inlet air temperature increased. The bulk density, moisture content and water activity of powders tended to decrease with the increase of inlet air temperature. In contrast, the powder yield increased with increasing of inlet air temperature. Furthermore, characteristics of the powder particulates were spherical with smooth surfaces for all treatments but when the inlet air temperatures was high the particles has deeper surfacial grooving and shriveled, especially for sample F1.